Pelayanan Administrasi Terpadu Kecamatan Percut Sei Tuan - Muhammad, Zatria; Syah, Rahmad (Universitas Medan Area, 2025)
The lack of implementation of procedures in the process of solving land deeds causes services to be less effective and prone to errors in writing archive data due to the manual process using a special agenda book. This research aims to build a web-based information system to improve efficiency and accuracy in the process of solving land deeds at the Percut Sei Tuan Sub-district Office. The system is designed to replace the manual methods that have been used, which often lead to delays, duplication of data, and inaccuracies in the management of archives. Using technologies such as PHP, MySQL, and Bootstrap5, the system allows for automatic data input, faster file checks, and the creation of structured periodic reports. The system is also equipped with an automatic land deed numbering feature to prevent data duplication and make it easier to track records. The results of the study show that the system developed is able to improve the work efficiency of government staff and provide convenience for the community in applying for land deed solutions. This system is expected to be a modern solution to support better administrative services in Percut Sei Tuan District.